2003
DOI: 10.1038/sj.bjp.0705564
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 3′, 5′ cyclic monophosphate attenuates the production of fibronectin in the glomeruli of anti‐glomerular basement membrane antibody‐associated nephritic rats

Abstract: 1 Excessive production of extracellular matrix is thought to be involved in the progression of glomerulonephritis and glomerulosclerosis. In chronic glomerulonephritis, fibronectin has been shown to accumulate in the glomeruli, accompanied by cell proliferation. 2 Glomerulonephritis was induced in rats by the injection of anti-glomerular basement membrane antibody. The rats showed proteinuria and histological alterations in the glomeruli. An increase in fibronectin levels in the culture medium of isolated neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…1B). The present findings are consistent with the previous reports using the glomeruli isolated from anti-glomerular basement membrane nephritic rats (10). Both EP 2 and EP 4 receptors are coupled with Gs protein in the cell membrane and generate cyclic AMP (21).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…1B). The present findings are consistent with the previous reports using the glomeruli isolated from anti-glomerular basement membrane nephritic rats (10). Both EP 2 and EP 4 receptors are coupled with Gs protein in the cell membrane and generate cyclic AMP (21).…”
Section: Discussionsupporting
confidence: 83%
“…1C). Cyclic AMP suppresses the excessive production of fibronectin in rat nephritic glomeruli (10) and recovers the function of injured spinal cord (23). Hence, we performed experiments to elucidate the anti-nephritic effect of an EP 4 -receptor agonist in the development of anti-glomerulus antibody-associated nephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin e 2 stimulates production of cyclic amP via eP2 and eP4 prostaglandin e receptors in isolated glomeruli [6,7,14]. we have demonstrated that isolated glomeruli generate prostaglandin e 2 and that a-Bsa increases the expression of cyclooxygenase-2 mrNa and cyclooxygenase-2 activity followed by the expression of prostaglandin e 2 [5].…”
Section: Discussionmentioning
confidence: 90%
“…The glomeruli were isolated with two kinds of nylon mesh (90-and 38-mm) and a magnet [7]. The purity of the glomeruli was more than 95% as observed under a light microscope.…”
Section: Isolation Of Glomerulimentioning
confidence: 99%